LAPORAN KEUANGAN SEBAGAI ALAT PERTANGGUNGJAWABAN PEBISNIS DI KOTA SURAKARTA - Eko Meiningsih Susilowati (KELOLA, 2015)
This study aims are to determine how financial statements used as a tool of accountability of businessmen. This study uses primary data. The population in this study are the businessmen in Surakarta. While the sample are the businessmen who engaged in services and trade in Surakarta. Samples were selected using proportional random sampling. The analysis uses percentages.The results showed that the majority of businesses in Surakarta are familiar with the financial statements and has been implementing the financial statements as a liability. Although they present the financial statements in the form of incomplete financial statements. Financial reports they use to facilitate calculating the level of profitability (profit company) and the company's level of risk. Most of the financial statements also provide information related to decision making for businesses in Surakarta. Keywords: laporan keuangan, pertanggungjawaban